Imagens movimentícias: quando a fotografia tangencia o cinema - Menezes, Allan Gomes (2022)
This dissertation aims to understand what are the plastic, conceptual and media changes that come from a photographic image when adding a very discrete and subtle movement to its frame, making it ambiguous between the static and the movement. This provokes some disorientation in the viewers, incapable of initially recognizing its temporality. Such discussion is made possible by using as subject the works ''Frutos Estranhos'' (2006) by Rosângela Rennó and ''Arvorar'' (2012) by Kátia Maciel. We will start from Vilém Flusser's concept of 'technical images', as it comprises both photography and cinema, in order to understand how these characteristics dilute among these images. Raymond Bellour's concept of 'inter-images' will be the starting point for understanding the entanglement of images with distinct temporalities and how our objects stand out for being far too thinly hybridized. To understand these images we will start a dialogue between concepts derived from both film and photography; when interlacing them, we sought out to make the form of writing here closer to the form of the aforementioned works, thus creating a hybrid analysis, akin to these works, not without mentioning the video and the new media as mediators of such hybridization. We will also consider images belonging to non-artistic fields, as we understand that the production of images in general is connected. In order to demonstrate the experiences that surround the objects, we will situate two great moments of artistic production, the modern and contemporary projects, for this, we will use contributions from authors such as Maurício Lissovsky, Jacques Aumont, André Bazin, Arlindo Machado, Philippe Dubois, among others. To understand these works question both languages approached, we will dive into their devices, their consolidated forms and their reading by the public. For this, we will rely on the ideas of André Parente, Antonio Fatorelli, Lucia Santaella, Roland Barthes, among others. Thus, a thorough analysis of these objects focused on their borderline temporality is feasible, relating it to other issues present in the works, as well as enabling an understanding of the form and context in which they are produced and what their effects on the public are. KEYWORDS: Between-the-images; Contemporary Photography; Cinema